Gate-tunable high magnetoresistance in monolayer Fe3GeTe2 spin valves. Issue 44 (4th November 2020) - Yang, Jie; Quhe, Ruge; Liu, Shiqi; Peng, Yuxuan; Sun, Xiaotian; Zha, Liang; Wu, Baochun; Shi, Bowen; Yang, Chen; Shi, Junjie; Tian, Guang; Wang, Changsheng; et al.
Abstract : Here we design a monolayer Fe3 GeTe2 spin-valve device by attaching two ends to ferromagnetic electrodes. A high magnetoresistance of ~ 390% is obtained and significantly increased to 450 ~ 510% after the gates are introduced. Abstract : Ferromagnetic order in two-dimensional (2D) van der Waals crystals has been attracting much attention recently. Remarkably, room temperature metallic ferromagnetism is realized in 2D Fe3 GeTe2 . Here we design a monolayer (ML) Fe3 GeTe2 spin-valve device by attaching two ends to ferromagnetic electrodes and applying a magnetic field to these ferromagnetic electrodes. We investigate the spin-involved transport characteristics of such a spin valve by using ab initio quantum transport simulation. A high magnetoresistance of ∼390% is obtained and significantly increased to 450–510% after the gates are introduced. The magnetoresistance of the ML Fe3 GeTe2 spin valve is insensitive to the strain modulation. Our study provides a potential option for magnetic storage applications and will motivate further studies in spintronics based on this class of materials.